As ausências e elos faltantes das análises regionais no Brasil e a proposiç\~ao de uma agenda de pesquisas de longo prazo - Carlos Antônio Brand\~ao (Instituto de Pesquisa Econômica Aplicada (IPEA), 2019)
– This study presents a typology designed to investigate territories impacted by public policies through the 2003-2015 period. For such, it was done a mapping of analysis and of stylized facts that represent the most relevant spatial transformations due to public and private expenditures and investments.
Keywords: O2; R5; R58; 330; regional development; regional policies; public policies